Bifurcations of limit cycles for a perturbed cubic system with double figure eight loop - Zhang, Tongua; Zang, Hong; Tade, Moses O. (World Scientific Publishing, 2013)
This paper is concerned with the distribution and number of limit cycles for a cubic Hamiltonian system under cubic perturbation. The fact that there exist seven limit cycles is proved. The different distributions of limit cycles are given by using the methods of bifurcation theory and qualitative analysis, and the distributions of seven limit cycles are newly established.